Teknik “Clark’s Rule” dalam bidang Kedokteran Gigi - Merry Annisa Damayanti; Ria Noerianingsih Firman; Suhardjo Sitam (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2019)
Objectives: The purpose of this study is to see how far the Clark's Rule technique (Same Lingual Opposite Buccal) can solve the problem of objects that coincide to each other. Literature Review: Various radiographic techniques can be used in dental photographs consisting of periapical bisecting and parallel photos. Both radiographic techniques produced two-dimensional images. In some cases, objects that often coincide were found and often became problem where the desired object was not visible. The technique that can be used to view object that coincide was Clark's Rule Technique (Same Lingual Opposite Buccal). This article was a literature review that reviews the Clark's Rule technique which would discuss the strengths, weaknesses and techniques of doing this method. Conclusion: The results of the photo radiograph on the Clark's Rule technique (Same Lingual Opposite Buccal) could see the object image of two objects that coincides. The conclusion of this article was the Clark’s Rule technique (Same Lingual Opposite Buccal) can complement the shortcomings of periapical bisecting and parallel photos.